2019
DOI: 10.1590/1516-3180.2018.0316240119
|View full text |Cite
|
Sign up to set email alerts
|

A novel simplified scoring system for predicting mortality in emergency colorectal surgery: prediction model development

Abstract: Despite advances in surgical approaches, emergency colorectal surgery has high mortality and morbidity. 1 The mortality rates after emergency colorectal surgery range from 2.3% to 80%. 2,3 This wide range is secondary to the expertise of the surgical center and the patients' comorbidities. Colorectal emergency situations such as diverticulitis, trauma and ischemia may be related to either benign or malignant etiologies. 3 Colorectal cancer is the reason behind colorectal emergencies in 85% of the cases, with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…Another study reports compatible results (22). Despite these results, we should keep in mind the possibility of inter-observer variability while talking about ASA scores and giving place in clinical judgment (23). On the other hand, in terms of preexisting comorbidities, COPD was associated with mortality in univariate analysis, but that relationship was not supported in multivariate analysis in our study.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Another study reports compatible results (22). Despite these results, we should keep in mind the possibility of inter-observer variability while talking about ASA scores and giving place in clinical judgment (23). On the other hand, in terms of preexisting comorbidities, COPD was associated with mortality in univariate analysis, but that relationship was not supported in multivariate analysis in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…While our power and time are limited, we want to get to know the patient in the most accurate way with the least variable. And the quest for the best continues (23). The learnings in seeking the best offer the opportunity to guide surgical training and assess the quality of surgical care.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that major complications were reported in patients who underwent PR operations compared to the AC procedure. Although NSQIP was used for CRS, numerous critical variables were missing from this procedure which include crucial oncologic data pertaining to colorectal cancer [6].…”
Section: Discussionmentioning
confidence: 99%